2003
DOI: 10.1128/jb.185.4.1245-1252.2003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Binding and Transcriptional Activation by the LysR-Type Transcriptional Regulator CbbR of Xanthobacter flavus

Abstract: The LysR-type transcriptional regulator CbbR controls the expression of the cbb and gap-pgk operons in Xanthobacter flavus, which encode the majority of the enzymes of the Calvin cycle required for autotrophic CO 2 fixation. The cbb operon promoter of this chemoautotrophic bacterium contains three potential CbbR binding sites, two of which partially overlap. Site-directed mutagenesis and subsequent analysis of DNA binding by CbbR and cbb promoter activity were used to show that the potential CbbR binding seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 28 publications
2
65
0
1
Order By: Relevance
“…The gel shift assay showed that CbbR1 bound to the overlapping promoter region between cbbLS-1 and cbbR1, suggesting that the expression of CbbR1 is subjected to autoregulation. Negative autoregulation has also been demonstrated for the LTTR including CbbR (Schell, 1993;Vichivanives et al, 2000;van Keulen et al, 2003). The amount of the cbbRm transcripts did not vary significantly under any of the CO 2 conditions.…”
Section: Expression Analyses Of Cbbr1 and Cbbrmmentioning
confidence: 76%
See 3 more Smart Citations
“…The gel shift assay showed that CbbR1 bound to the overlapping promoter region between cbbLS-1 and cbbR1, suggesting that the expression of CbbR1 is subjected to autoregulation. Negative autoregulation has also been demonstrated for the LTTR including CbbR (Schell, 1993;Vichivanives et al, 2000;van Keulen et al, 2003). The amount of the cbbRm transcripts did not vary significantly under any of the CO 2 conditions.…”
Section: Expression Analyses Of Cbbr1 and Cbbrmmentioning
confidence: 76%
“…Another possible explanation for the cross-regulation is that an accumulation of certain intermediates or a change in certain cellular states caused by the loss of CbbLS-1 and/or CbbM is the trigger for the induction of another RubisCO. It has been reported that the DNA binding of CbbR is altered in the presence of certain metabolites in other bacteria (van Keulen et al, 1998(van Keulen et al, , 2003Grzeszik et al, 2000;Terazono et al, 2001;Dubbs et al, 2004). In R. capsulatus, the binding of both CbbRI and CbbRII to their cognate promoter was enhanced in the presence of certain metabolites formed by the CBB cycle, as well as other intermediates, including ribulose-1,5-bisphosphate, 3-phosphoglycerate and PEP (Dubbs et al, 2004).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Co-inducers are recognized as being important for the function of LTTRs and often appear to contribute to a feedback loop in which a product or intermediate of a given metabolic/synthesis pathway (usually activated by an LTTR) acts as the co-inducer necessary for transcriptional activation or repression ( Fig. 1) (Celis, 1999;van Keulen et al, 2003;Picossi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%